Dengue virus non-structural protein 1: a pathogenic factor, therapeutic target, and vaccine candidate - Chen, Hong-Ru (J Biomed Sci, 2018)
Dengue virus (DENV) infection is the most common mosquito-transmitted viral infection. DENV infection can cause mild dengue fever or severe dengue hemorrhagic fever (DHF)/dengue shock syndrome (DSS). Hemorrhage and vascular leakage are two characteristic symptoms of DHF/DSS. However, due to the limited understanding of dengue pathogenesis, no satisfactory therapies to treat nor vaccine to prevent dengue infection are available, and the mortality of DHF/DSS is still high. DENV nonstructural protein 1 (NS1), which can be secreted in patients’ sera, has been used as an early diagnostic marker for dengue infection for many years. However, the roles of NS1 in dengue-induced vascular leakage were described only recently. In this article, the pathogenic roles of DENV NS1 in hemorrhage and vascular leakage are reviewed, and the possibility of using NS1 as a therapeutic target and vaccine candidate is discussed.